Reversal of Oxidative Stress by Histamine H3 Receptor-Ligands in Experimental Models of Schizophrenia - Mahmood, D.; Khanam, R.; Pillai, K. K.; Akhtar, M. (Arzneimittelforschung, 2012)
Schizophrenia (SCZ) is a debilitating disorder afflicting around 1% of the world population. Recent literature reveals oxidative injuries contribute enormously to the pathophysiology of SCZ alongside other psychopathological disturbances. Histamine H3R-antagonists have shown dual mechanism of action in experimental models of SCZ. Firstly it prevents oxidative stress and secondly alleviates schizophrenic symptoms, particularly the negative symptoms and cognitive deficits. In the present study, histamine H3R-antagonists used were ciproxifan (3.0 mg/kg, ip) and clobenpropit (15 mg/kg, ip) markedly controlled the elevated levels of various oxidative stress markers, for example, thiobarbituric acid reactive substance (TBARS), glutathione (GSH), superoxide dismutase, catalase, etc., as a result of augmented oxidative stress in the experimental models of SCZ such as amphetamine (0.5 mg/kg, sc) and dizocilpine (MK-801) (0.2 mg/kg, ip) induced locomotor hyperactivity, apomorphine (1.5 mg/kg, sc) induced climbing behavior and haloperidol (2.0 mg/kg, po) induced catalepsy. The results of the present study revealed that H3R-antagonists possess antioxidant activity and could serve with dual mechanism by supplementing antioxidant needs of SCZ and at the same time controlling symptoms of SCZ.
Keywords: schizophrenia; oxidative stress; histamine H3 antagonists; amphetamine; MK-801